The Effectiveness of Google Classroom Learning Applications on Student Learning Outcomes - Anas, Muh; Murti, Warda (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This research aimed to determine the effectiveness of Google Classroom learning on the learning outcomes of students of STKIP Pembangunan Indonesia at the Biology Study Program. The benefit of this research is that the results are expected to contribute to the teaching and learning process that lecturers will carry out, especially the application of the Google Classroom in improving students’ learning outcomes. The researchers employed the quantitative approach with a pre-experimental design of one group pretest-posttest, which provided a pretest before the treatment. After the treatment, the researchers administered a posttest on the Vertebrate Zoology course. The data collection technique applied in this research was a description test administered during the pretest and posttest. This research found that the students’ learning outcomes in the pretest were 36% in the completeness level. There was an increase in the posttest with a 72% completeness level. The results of hypothesis testing using an independent sample t-test obtained value of 3,149, which was higher than tobserved of 1.67. The results showed that students’ learning outcomes after using Google Classroom were significantly better than before the application of Google Classroom. This research proved that Google Classroom was an online learning method that can improve the quality of education, especially students’ learning outcomes, and could overcome the constricted learning process with the availability of actual classrooms.